Enhancement of bioelectricity production from Soil Microbial Fuel Cell (SMFC) by additional glucose, nutrient broth and Escherichia coli bacteria - Shahirah Raiyan Saleh,; Nur Kamilah Abd Jalil,; Umi Aisah Asli,; Aidee Kamal Khamis,; Anwar Johari,; Nadzreeq Nor Majid,; Sasongko, Nugroho A.; Ramadhan, Wisnu (Penerbit Universiti Kebangsaan Malaysia, 2019)
Soil Microbial Fuel Cell (SMFC) is a device that using bacteria in soils as a biocatalyst. These bacteria, called exoelectrogenic bacteria are oxidizing organic substrates to release electrons, which then harvested in an external circuit to produce bioelectricity. Despite all the potential, the bioelectricity production from soils is still low and its relation with SMFC conditions is uncertain. Hence, the main objective in this study is to enhance and stabilize the bioelectricity production of SMFC by additional glucose, nutrient broth and Escherichia coli (E. coli) as exoelectrogenic bacteria. A number of factors of SMFC performance were first identified to be preliminary investigated, that is the type of electrode, water addition to soil and distance between anode to cathode. It has been established in this study to use SMFC with the configuration of 9.5 cm in diameter and 15 cm height of the plastic container, with the 12 cm distance between carbon felt of anode and cathode. The electricity produced was measured by using a multimeter in term of voltage reading (mV). From this study, the highest bioelectricity produced was obtained from SMFC using nutrient broth with a maximum voltage of 700 mV. It has found that the additional E. coli bacteria did not increase the bioelectricity production. The use of E. coli needed to be combined with nutrient broth in order to achieve high and stable bioelectricity. It can be suggested that the indigenous bacteria that exist in the soils possibly played the role in producing bioelectricity.